Immunoglobulin-G level on aggressive periodontitis patients treated with clindamycin - Agung Krismariono (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Aggressive periodontitis might occur as a result of complex interplay between bacteria and host defence, therefore, the host susceptibility plays important role. Antimicrobial agents that could enhance host defence are required. Clindamycin might influence host defence. Purpose: The purpose of this study was to determine the influence of clindamycin on level of Immunoglobulin-G (IgG) patients with aggressive periodontitis, and its mechanism. Methods: This study used the pre-test post-test control group design. Eighteen aggressive periodontitis patients were divided into 2 groups at random. Group 1 (treatment): 9 aggressive periodontitis patients were given with clindamycin of 150mg orally, 4 times a day, for 7 days. Group 2 (control): 9 aggressive periodontitis patients were given with tetracycline of 250mg orally, 4 times a day for 12 days, and then metronidazole of 200mg orally, 3 times a day for 10 days. Blood sample was collected from vena cubiti mediana. Level of IgG was measured at base line and day 28. Data were analyzed statistically by using t-test (a = 0.05). Result: Examination for IgG level showed there was significant difference between pre-test and post-test (p < 0.05). Level of IgG was significantly increased after therapy, both in treatment and control group. The increase of IgG level in treatment group was not different significantly from control group (p>0.05). Conclusions: This study shows that clindamycin can be used as drug of choice for the treatment of aggressive periodontitis since clindamycin can improve the immunity status of aggressive periodontitis patients.